2017
DOI: 10.1016/j.amepre.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender and Physical Performance on Injuries: An Army Study

Abstract: When accounting for age, body fat, physical performance, and occupational physical demand, there was no gender difference in the likelihood of injury among Soldiers. Although women, on average, have lower aerobic and muscular performance than men, results suggest men and women of similar physical performance experience similar injury likelihood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 25 publications
(42 reference statements)
6
60
3
1
Order By: Relevance
“…Similar to the present study, Bell et al 31 reported a two-fold greater injury risk with female sex, when fitness was not taken into account. However, consistent with the present study, previous research has not found female-sex to be an independent risk factor, where the sex and injury risk relationship appeared to be explained by poorer aerobic fitness 1,31,34 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the present study, Bell et al 31 reported a two-fold greater injury risk with female sex, when fitness was not taken into account. However, consistent with the present study, previous research has not found female-sex to be an independent risk factor, where the sex and injury risk relationship appeared to be explained by poorer aerobic fitness 1,31,34 .…”
Section: Discussionsupporting
confidence: 90%
“…Sex has previously been shown to be a risk factor for injury in military training programmes, with female recruits being at significantly greater risk compared with male recruits 1,10, [30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…The gender equality in service-related injuries that we observed in our study is contradictory to previous military research [54, 55]. We did not have the data to conclude whether the two genders had distinct positions or were assigned to different tasks and operations in the military, which could influence service-related injuries.…”
Section: Discussioncontrasting
confidence: 99%
“…From the 43 articles, 18 articles were retained. Among those 18 articles, there were 15 cohort studies (1,3,9,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and three cross-sectional studies (1,2,34,35). Methodological quality overall was considered 'good' (80%), with cohort studies tending to score higher (82%), than cross-sectional studies (68%).…”
Section: Resultsmentioning
confidence: 99%
“…Methodological quality overall was considered 'good' (80%), with cohort studies tending to score higher (82%), than cross-sectional studies (68%). Seven studies assessed injury risk in basic training (16, 22, 25-27, 29, 36), three studies during Advanced Individual Training (AIT) (23,24,35), three studies in enlisted personnel more broadly (1,3,34), three studies during deployments (2,32,33), one study during o cer training (9), and one during the rst 183 days of service (31). Sixteen of the included studies were conducted in the United States military (1-3, 9, 22-24, 26, 27, 29, 31-36), one in the Israel Defense Forces (30), and one in the British Army (25).…”
Section: Resultsmentioning
confidence: 99%